Unveiling the trophic dynamics and ecological roles of demersal fish in Hong Kong: A metabarcoding and isotope analysis approach - Hei-Ching Wong; Chun-Ming How; Kelly Su; Leyi Xi; Chien-Hsiang Lin; Ming-Tsung Chung; Jian-Wen Qiu; Chris Kong-Chu Wong; Jill Man-Ying Chiu (PLoS ONE, 2025)
This study provides a comprehensive examination of the trophic ecology and feeding dynamics of 16 demersal fish species inhabiting the southern and southwestern waters of Hong Kong, utilizing advanced 12S and COI gut content metabarcoding alongside stable isotope analysis. Dietary dissimilarities, primarily driven by Decapoda and fish, are significant among species. Network plots further highlight unique predator-prey interactions. Eight species, including horn dragonet Callionymus curvicornis and Japanese butterflyray Gymnura japonica , are identified as piscivores, primarily preying on demersal fish, while six species such as rough flathead Grammoplites scaber and Japanese flathead Inegocia japonica are classified as crustacean feeders, focusing on Decapoda. Notably, spotted sicklefish Drepane punctata and goatee croaker Dendrophysa russelii exhibit unique feeding behaviors, relying on brittle star and Bivalvia, respectively, and demonstrate non-selective feeding patterns that do not prioritize dominant environmental species. This diverse range of prey consumption highlights the critical roles these fish play in regulating demersal fish and benthic invertebrate communities. The study also reveals clear trophic niche partitioning with low isotope niche overlap, predominantly below 55.30%, except for a notable overlap of 72.91% between bartail flathead Platycephalus indicus and goatee croaker D. russelii . Our results established essential baseline data on trophic niche diversification and resource partitioning through varied dietary preferences, facilitating coexistence and resilience within the ecosystem. This research serves as a foundational assessment of the trophic dynamics and ecological stability in Hong Kong’s marine ecosystems, offering valuable insights into anthropogenic pressures and guiding the development of specific conservation strategies aimed at preserving fish biodiversity and sustaining global fisheries.